Self-help interventions for smoking cessation - Lancaster, T; Stead, L F (Cochrane database of systematic reviews, 2000)
Many smokers give up smoking on their own, but provision of materials giving advice and information may assist them and increase the number who quit successfully. The aims of this review were to determine the effectiveness of different forms of self-help materials, compared with no treatment and with other minimal contact strategies; the effectiveness of adjuncts to self-help, such as computer generated feedback, telephone hotlines and pharmacotherapy; and the effectiveness of approaches tailored to the individual compared with non-tailored materials. We searched the Cochrane Tobacco Addiction Group trials register. Date of the most recent search September 1999. We included randomised trials of smoking cessation with follow-up of at least six months, where at least one arm tested a self-help intervention. We defined self-help as structured programming for smokers trying to quit without intensive contact with a therapist. We extracted data in duplicate on the type of subjects, the nature of the self-help materials, the amount of face to face contact given to subjects and to controls, outcome measures, method of randomisation, and completeness of follow-up. The main outcome measure was abstinence from smoking after at least six months follow-up in patients smoking at baseline. We used the most rigorous definition of abstinence in each trial, and biochemically validated rates when available. Where appropriate, we performed meta-analysis using a fixed effects model. We identified forty-five trials. Twenty seven compared self-help materials to no intervention or tested materials as an adjunct to advice. In nine trials in which self-help was compared to no intervention there was a pooled effect which just reached statistical significance (odds ratio 1.23, 95% confidence interval 1.02 to 1.49). There was no evidence of benefit from adding self-help materials to face to face advice, or to nicotine replacement therapy. There was evidence from eight trials using materials which were tailored for the characteristics of individual smokers that such personalised materials were more effective than standard materials (odds ratio 1.41, 95% confidence interval 1.14 to 1.75). Adding follow-up telephone calls from counsellors also appeared to increase quitting (odds ratio 1.62, 95% confidence interval 1.33 to 1.97). One trial of offering access to a hotline also showed an effect. Self-help materials may provide a small increase in quitting compared to no intervention. There is no evidence that they have an additional benefit over other minimal interventions such as advice from a health care professional, or nicotine replacement therapy. There is evidence that materials tailored for individual smokers are more effective.